“When he should have said...” The treatment of humour παρ’ ὑπόνοιαν in the Aristophanic Scholia - Willi, A (De Gruyter, 2024)
While the Aristophanic scholia do not normally pay much attention to the mechanisms of verbal humour, there are numerous annotations pointing out jokes “against expectation”. The term typically used for this common phenomenon is παρ᾿ ὑπόνοιαν rather than παρὰ προσδοκίαν, although the latter also occurs a few times, probably under the influence of rhetorical teaching. The scholiasts’ general awareness of the feature, and their insistence on it, does not, however, go hand in hand with any in-depth analysis; much rather, παρ᾿ ὑπόνοιαν risks being used as a cover-all label for a variety of comic devices and without much consideration being given to its contextual appropriateness. Moreover, there is some evidence to suggest that explanations by means of παρ᾿ ὑπόνοιαν could be a last resort when difficult passages could not be explained in a more “sophisticated” manner.